2011
DOI: 10.1007/s12094-011-0706-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal niches of bone marrow in cancer

Abstract: Over the last decade, genetic and cell biology studies have indicated that tumour growth is not only determined by malignant cancer cells themselves, but also by the tumour microenvironment. Cells present in the tumour microenvironment include fibroblasts, vascular, smooth muscle, adipocytes, immune cells and mesenchymal stem cells (MSC). The nature of the relationship between MSC and tumour cells appears dual and whether MSC are pro- or anti-tumorigenic is a subject of controversial reports. This review is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…[56][57][58]59 Cancer stem cells may remain quiescent in the BM niche for long periods, 36 migrating to a future tumor site and establishing new malignancy even years after the primary tumor was eliminated. 1,36,37 In our study, cancer cells cultured on 3D POR biolattice showed upgraded tumorigenic capacity, as manifested in their elevated migration potential towards MSCs, which served as a migration trigger (Figure 2). We suggest that the calcium providing milieu may induce a cancer stem cell-like state, endowing cells cultivated on POR scaffolds with greater tumorgenic potential.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…[56][57][58]59 Cancer stem cells may remain quiescent in the BM niche for long periods, 36 migrating to a future tumor site and establishing new malignancy even years after the primary tumor was eliminated. 1,36,37 In our study, cancer cells cultured on 3D POR biolattice showed upgraded tumorigenic capacity, as manifested in their elevated migration potential towards MSCs, which served as a migration trigger (Figure 2). We suggest that the calcium providing milieu may induce a cancer stem cell-like state, endowing cells cultivated on POR scaffolds with greater tumorgenic potential.…”
Section: Discussionmentioning
confidence: 60%
“…34 Bone marrow attracts homing tumor cells, 1,35 providing them with a calcium rich shelter. 36,37 In light of the proven involvement of calcium in enhanced malignancy capacity, it seems likely that BM induces changes in the tumorigenicity of Cancer Cells (CCs). To test this hypothesis, it would be necessary to study tumor related processes in an adequate 3D model with a calcium rich milieu.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in vivo models capable of integrating both the nature of the target cell for transformation, the underlying oncogenic lesions, and the influence of the microenvironment will constitute a valuable model to study tumor biology and to assess potential novel therapeutic approaches [48]. Solid evidence indicates that MSCs and/or MSC-derived progenitors represent the TIC for human sarcomas [1][2][3][4]. Likewise, normal, nonmalignant MSC-like cells have been isolated at high frequencies from primary OS samples, suggesting that normal MSCs could be recruited to the microenvironment of OS and play a role in the development of the disease [49].…”
Section: Discussionmentioning
confidence: 99%
“…Solid evidence indicates that MSCs and/or MSC-derived progenitors represent the TIC for human sarcomas [1][2][3][4]. Likewise, normal, nonmalignant MSC-like cells have been isolated at high frequencies from primary OS samples, suggesting that normal MSCs could be recruited to the microenvironment of OS and play a role in the development of the disease [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation